687.141.017.872.004.15 Compression sports wear: ANALYSIS OF ELASTIC FABRICS FOR COMPRESSION SPORTSWEAR IN THE NEW ASSORTMENT - Monnopov, Joxongir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article considers the most important factors in the analysis of the modern range of materials with compressive properties. For the design of compression sports goods, fabric samples were selected and analyzed for hygienic indicators and mechanical properties with the results of experimental tests using standard methods. The characteristics of the analyzed fabrics are expressed in the table, and the YG026T device was used to evaluate the compressive strength of the fabrics. The analysis of the elasticity of the experimental samples was carried out under a force of 6N, and the results of the evaluation of the half-cycle deformations are presented in the elongation diagram.